2019
DOI: 10.1080/17453674.2019.1605692
|View full text |Cite
|
Sign up to set email alerts
|

Marker-based versus model-based radiostereometric analysis of total knee arthroplasty migration: a reanalysis with comparable mean outcomes despite distinct types of measurement error

Abstract: (2019) Marker-based versus modelbased radiostereometric analysis of total knee arthroplasty migration: a reanalysis with comparable mean outcomes despite distinct types of measurement error,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…An incorrect rotational alignment of the reference model can lead to incorrect rotations and hence inaccurate translation measurement. This effect of rotation on translation is explained by Beardsley et al and Van Hamersveld et al [ 21 , 22 ] Therefore, striving for a well three-dimensional spread and stable rigid body as a reference for migration calculation is still important, even if rotations are left out of consideration. However, the small size of the surrounding bone makes it difficult to ensure this in the TMC joint.…”
Section: Discussionmentioning
confidence: 99%
“…An incorrect rotational alignment of the reference model can lead to incorrect rotations and hence inaccurate translation measurement. This effect of rotation on translation is explained by Beardsley et al and Van Hamersveld et al [ 21 , 22 ] Therefore, striving for a well three-dimensional spread and stable rigid body as a reference for migration calculation is still important, even if rotations are left out of consideration. However, the small size of the surrounding bone makes it difficult to ensure this in the TMC joint.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it would be of interest to analyze the effect of certain biomarkers and bone mineral density on migration in such a large group of patients with long-term migration data. Another limitation was that different RSA methods were used across studies, which might result in patients from 1 study being more susceptible to certain types of measurement errors than others 13 . However, we did statistically correct for clustering of patients within each study.…”
Section: Discussionmentioning
confidence: 99%
“…In uncemented components, high initial migration may also be physiological and merely part of a biphasic migration pattern with high initial migration (i.e., a settling phase) before stabilizing 2,6 . Previous long-term follow-up RSA studies have shown that long-lasting biological fixation can be achieved despite high initial migration in both uncemented components with a hydroxyapatite coating and uncemented components made of highly porous metal 12,14,26 . Uncemented components without an osseointegration-promoting surface, however, more often show a prolonged settling phase (possibly >2 years) or may not stabilize at all 14,27 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations